2015
DOI: 10.1007/s00127-015-1047-9
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of young Adult Social well-being and Health (DASH) study: diversity, psychosocial determinants and health

Abstract: PurposeThe Determinants of young Adult Social well-being and Health longitudinal study draws on life-course models to understand ethnic differences in health. A key hypothesis relates to the role of psychosocial factors in nurturing the health and well-being of ethnic minorities growing up in the UK. We report the effects of culturally patterned exposures in childhood.MethodsIn 2002/2003, 6643 11–13 year olds in London, ~80 % ethnic minorities, participated in the baseline survey. In 2005/2006, 4782 were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…In addition, the male sex was the strongest predictor for smoking in the regression analyses, especially in healthy individuals. This is probably related to cultural factors, in that smoking behavior and its sex differences are diverse among ethnicities ( Alvarado and Breslau, 2005 ; Harding et al, 2015 ; Higgins et al, 2015 ). This study presented data about smoking in patients with schizophrenia and healthy individuals of Japanese ethnicity, and the findings are consistent with a prior Japanese study which also reported that the male sex was most strongly associated with smoking ( Shinozaki et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the male sex was the strongest predictor for smoking in the regression analyses, especially in healthy individuals. This is probably related to cultural factors, in that smoking behavior and its sex differences are diverse among ethnicities ( Alvarado and Breslau, 2005 ; Harding et al, 2015 ; Higgins et al, 2015 ). This study presented data about smoking in patients with schizophrenia and healthy individuals of Japanese ethnicity, and the findings are consistent with a prior Japanese study which also reported that the male sex was most strongly associated with smoking ( Shinozaki et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results showed, that-in line with other studies [50,51]-ethnic minority adolescents reported better mental health than White British suggesting that this resilience might be explained by cultural factors. However, a less positive result could be detected for cardio-respiratory health outcomes such as ethnic minority groups had higher blood pressure compared to White British [34].…”
Section: Green Et Al 2014 [40] London Ukmentioning
confidence: 93%
“…About one-third of the sample was overweight or obese at both ages. Overweight, which was related to poor nutritional habits (cited earlier) in early adolescence, was associated with early markers of CVD risk (28) . Family activities (26) included watching television or videos, playing indoor games, eating a meal, going for a walk or playing sports, visiting friends or relatives and going other places; a score was derived based on frequencies of all six activities, with a higher score indicating better family connectedness.…”
Section: Ethnicity and Overweightmentioning
confidence: 89%